Oltre un solo Novecento. L’architettura modernista di Tashkent / More than one 20th-century. Tashkent Modernist Architecture - Del Curto, Davide (Restauro Archeologico, 2025)
Tashkent, the capital of Uzbekistan is an outstanding example of how 20th-century architecture was used to shape an early cosmopolitan capital, i.e., a vibrant mosaic of cultures and ethnicities, following the political and social shift in Central Asia under the Soviet period. Tashkent therefore testifies how modernization was a non-capitalist path towards development along the 20th century beyond Europe and the US, and how post-war architecture and urbanism accompanied the building of a new society under socialism. Having been the crossroads of cultures for centuries, Tashkent became the capital of so-called Russian Turkestan in 1867, as part of the ’Great Game’ rivalry between the Russian and British Empires over Central Asia. Industrialization began in the 1920s and was boosted as a result of World War II. An earthquake destroyed much of the city in 1966, and the subsequent reconstruction speeded up the modernization process and made Tashkent the fourth most populous city in the Soviet Union between the Thaw period and the fall of the USSR. This way, Soviet Tashkent restored Central Asia to its former transitional function on the Great Silk Road, a place where cultures, races, ideas, and languages intertwined. The city was to be both the Soviet gateway to Asia and a showcase of the ’Soviet Orient’, vivid proof of how socialism and modernism could adapt to any postcolonial scenario.